2022
DOI: 10.1007/978-3-030-90839-3_4
|View full text |Cite
|
Sign up to set email alerts
|

Compression of Dynamic Tactile Information in the Human Hand

Abstract: A key problem in the study of the senses is to describe how sense organs extract perceptual information from the physics of the environment. We previously observed that dynamic touch elicits mechanical waves that propagate throughout the hand. Here, we show that these waves produce an efficient encoding of tactile information. The computation of an optimal encoding of thousands of naturally occurring tactile stimuli yielded a compact lexicon of primitive wave patterns that sparsely represented the entire datas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…This likely arises from the mechanical attributes of the hand, which induces a ripple of vibration following even very localized touch, which will, in turn, cause a specific spatiotemporal pattern of mechanoreceptor activity across the entire hand (see also Fig. 4A) ( 6 , 8 ). At the cortical level, receptive fields can be complex and integrate information across a variety of receptor types ( 5 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This likely arises from the mechanical attributes of the hand, which induces a ripple of vibration following even very localized touch, which will, in turn, cause a specific spatiotemporal pattern of mechanoreceptor activity across the entire hand (see also Fig. 4A) ( 6 , 8 ). At the cortical level, receptive fields can be complex and integrate information across a variety of receptor types ( 5 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Shared interfinger representation may be the result of input synchronization: Manfredi and colleagues (6) have demonstrated that even passive stimulation of a part of the hand triggers extensive ripple effects across the skin [see also (7)]. Because these ripples activate mechanoreceptors on other fingers, even localized tactile stimulation elicits widely distributed peripheral responses, with distinct spatiotemporal patterns (8). Together with related findings characterizing the organizational features of the S1 hand map that are not necessarily anchored to topographic maps (9)(10)(11)(12), these results suggest that shared somatosensory processing of inputs from multiple skin surfaces across the hand is more prevalent than typically appreciated.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to SA1 and RA afferents, the information level for PC afferents was essentially constant for all density values considered across all tactile features. While this result might be taken to suggest that the PC population does not contribute information above that of a single afferent, there is evidence to suggest that PC populations might be important in different tactile contexts than the ones explored here: making contact with surfaces causes mechanical waves to spread throughout the hand, activating PC afferents as far away as the palm and their joint population activity carries information about how contact is made and other aspects of the grasp (34).…”
Section: Discussionmentioning
confidence: 85%
“…The sparsity condition ensures that the information is embedded in a population code with a minimum number of neurons active at any one time, leading to a more than 20-fold compression of images or audio waveforms without losing perceptual accuracy 25 . Similar efficient coding strategies have been observed in touch, and facilitate the classification of hand gestures from vibrotactile surface wave propagation 26 or to identify material properties from the vibrotactile signal they produce 27 .…”
Section: Efficient Coding Hypothesismentioning
confidence: 78%